Analysis of Students’ Errors in Solving Word Problem Related Graph - Khairiyah Rahma Lubis; Rahmah Johar; Andariah Andariah (Proceedings of AICS - Social Sciences, 2017)
Reading, interpreting and constructing graphs are important skills for junior high school students. The graph as a mathematical expression is important as graphs can represent or summarize data and communicate data for easy interpretation. The purpose of this study is to analyze the errors that occur in students in solving the word in class VIII-1 MTsN Model Banda Aceh. Data were obtained based on test of 36 students and continued by interview of five students. Based on the results of data analysis found that students’ make mistakes in solving word problem related to the graphs in either understanding or reading graphs or drawing graphs. Keywords:error analysis, word problem, graph.